The Effect of Red Paprika Juice (Capsium annum) Addition into the Feed to Brightness of The Red Comet Fish Colour (Carassium auratus) - Anisa Larasati Humairo; Muhammad Junaidi; Muhammad Marzuki (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
This study aims to determine the color change of comet fish (Carasium auratus) after being given additional feed in the form of red paprika juice. Measurement of the fish color was carried out every 10 days for 1 month and visual observations were made with digital photos and analyzed the colors using Adobe Photoshop CS4 software. In this study, different concentrations of paprika juice were used. This study used a completely randomized design (CRD).There were 5 treatments, namely P0 without the addition of red paprika juice (control), P1 with the addition of 2% paprika juice, P2 with the addition of 4% paprika juice, P3 with the addition of 6% paprika juice, and P4 with the addition of 8% paprika juice, which was performed on 3 times for each. The research data were analyzed using statistical analysis Unvariate One Way Analysis of Variance at 5% level with a 95% confidence interval. The results showed that the highest increase in color quality was obtained in the P3 treatment with an average value of 63.85 ÃÂ± 2.12, the highest specific weight growth rate was obtained in P3 treatment with an average value of 60.825 ÃÂ± 0.59 days, the highest specific length growth rate was obtained atP3 treatment with an average value of 1.37 ÃÂ± 0.28 grams, while at the survival rate there is a significant value or not significantly different. The conclusion of this study is the effect of adding red paprika juice in the feed affects the color quality and specific growth rate, while the survival rate is not affected. Furthermore, the dose of red paprika juice added to the feed can improve the color quality of comet fish with the highest value found in P3 (with the addition of 6% paprika juice), namely 63.85.